Communicative Language Teaching Paradigm - Cucu Sutarsyah (LINGUISTIKA, 2010)
The paradigm shift has occurred since more than 40 years. This shift covers almost all fields of science. As a tradition of revolutionary thinking, a paradigm shift also occurred in education, particularly in language education. This article contains a review of the process of paradigm shift in a communicative language teaching, namely the shift from positivism to post positivism. This discussion includes eight aspects of change, among others, Learner Autonomy, the essence a Social Learning, Curriculum Integration, Focus on Meaning, Diversity, Thinking Skills, Alternative Measurement, and Teachers as Co-LearnersIn fact the eighth aspects of paradigm were not fully implemented thoroughly in public education, particularly in the field of second language. Educators and other stakeholders have been trying to understand and implement the change by way of partial, rather than a holistic manner. The main purpose of this paper is to show that this change is important to improve the quality of learning a second language.